Estimates of Bowhead Whale (Balaena mysticetus) Numbers in the Beaufort Sea during Late Summer - Moore, Sue E.; Clarke, Janet T. (ARCTIC, 1991)
Broad estimates of bowhead whale numbers in Beaufort Sea outer continental shelf (OCS) waters were calculated based on raw counts of whales seen during aerial surveys conducted in late summer 1982-84, corrected by factors accounting for surface area not sampled, surfaced whales missed by observers, and whales too deep to be seen. Annual estimates ranged from roughly 700-1200 to 3000-3500 whales for the latter half of August and from 2000-2200 to 1600-2900 whales for the first half of September. Additionally, estimates of up to 3000 whales were calculated for subregions of the Beaufort Sea for two separate two-week periods, with adjacent-period estimates of only several hundred whales in the same subregions, implying that whale concentrations were highly transitory. The highest estimate (ca. 3500 whales) accounts for less than half of the estimated 7800 whales in the Bering Sea bowhead population. If the population estimate of 7800 whales is valid, then either a substantial number of whales summered outside Beaufort Sea OCS waters in 1982-84 or bowhead numbers are routinely underestimated by the methods used here, or some combination of both.Key words: bowhead whale, Beaufort Sea, outer continental shelf, abundance estimates, aerial surveys Mots clés: baleine franche, mer de Beaufort, au large du plateau continental, évaluations de la quantité, relevés aériens